If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19(8x + 3) = 0 Reorder the terms: 19(3 + 8x) = 0 (3 * 19 + 8x * 19) = 0 (57 + 152x) = 0 Solving 57 + 152x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-57' to each side of the equation. 57 + -57 + 152x = 0 + -57 Combine like terms: 57 + -57 = 0 0 + 152x = 0 + -57 152x = 0 + -57 Combine like terms: 0 + -57 = -57 152x = -57 Divide each side by '152'. x = -0.375 Simplifying x = -0.375
| 5x-(3x+7)=9+2(x-8) | | ax+bx+6=0 | | x=40-2x | | 3x+16=15x-68 | | (3w+2)(3w-2)=-w^2+26w-16 | | x^2-4y+6x+9=0 | | 5x+500=1700 | | 4xsquared+3x-8=0 | | (y-4)(y-3)=6 | | lg(x^2-4)=lg(4x+1) | | 2c+8=3e+15 | | 2/7x=5 | | 6y=2.4 | | 9+r=15 | | 61+x=7 | | 8+2(z-4)=-7z+7 | | cos^2x-5cosx-4=0 | | cosx^2-5cosx-4=0 | | 3y+4z=130 | | -3(-7x-6)+11x=14-(10x-19) | | -0.7=-0.7+0.6u | | 10-3(2r-1)=1 | | 5/2×2-7 | | 1/2(-10r) | | x=(x*4)-875 | | X/6=0.5 | | 15+(-18)=7x-3-6x | | ln(1/72)=y | | xsquare=40 | | 4x=1/10 | | 24s=528 | | 16n=192 |